ANALISIS KEBOCORAN HYDRAULIC MANIFOLD PADA PESAWAT AIRBUS 330 SERIES DI PT XYZ MENGGUNAKAN METODE RCFA - I Komang Gede Galang Aditya Wirama; Iwan Engkus Kurniawan; Fawwaz Yusa Gifari (Politeknik Negeri Sriwijaya, Indonesia, 2025)
The Airbus 330 series aircraft uses a hydraulic system to move various main components such as landing gear, flight control, and braking. In its operation, this system utilizes pressurized fluid transferred through the HP manifold to each user system. The Airbus 330 series aircraft has 3 HP manifold components installed in each system. Based on data from PT XYZ engineering, there have been 86 hydraulic leak problems that occurred in the HP manifold in the period from 2021 to 2024. Therefore, it is necessary to analyze and determine the cause using the Root Cause Failure Analysis (RCFA) method with pareto diagram tools, fishbone diagrams, and 5W + 1H. The results of the study found that there are 4 causes of leaks in the HP manifold, namely packing, connection, union, and clogging. The most dominant problem is caused by packing with a percentage of 82.56%. The results of the analysis using a fishbone diagram showed that leaks caused by packing occurred due to complacency, the use of manual torque wrenches when maintenance, the use of non-specific job card inspections in DVI, working outside the hangar at night, and the degradation of packing materials caused by the higher acidity of the hydraulic fluid. Higher acidity is the most influential factor in packing damage, causing leaks in the HP manifold. By using the 5W + 1H method, a repair proposal was obtained for the company in the form of creating an Engineering Order (EO) and making readjustments related to the maintenance program.